2021
DOI: 10.1590/1519-6984.227621
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological studies of red palm weevil Rhynchophorus ferrugineus, (Olivier) larvae and adults to evaluate certain nano pesticides

Abstract: Rhynchophorus ferrugineus (RPW) (Olivier) (Coleoptera: Curculionidae) is one of the most destructive pest of palm according to dozens of literature, a lot of effort have been made since three decades up to date to solve this problem, one of newest solution raised is using nano pesticides. Imidacloprid and Chloropyrophos and their nano form were tested against 10 days-old larvae and newly emerged adults of the red palm weevil. The pesticides had toxicological and pathological effects on Rh. ferrugineus larvae a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…The obtained results for pathological damage of treated RPW larvae, R. ferrugineus, revealed that midgut was sensitive to the tested insecticides. A similar result was obtained by (Abd El-Fattah et al, 2020) who reported that the damage included vacuolation of cytoplasm, analyzes and destroyed nuclei of the epithelial cells of RPW larvae treated with imidacloprid and chlorpyrifos and their nano form as well as by (Abdel-Ghaffar, 2004) from different insecticides against different insects. Also, (Ahmed, 1995) reported that the histopathological action of some pesticides was observed to cause epithelial cell expansion and the formation of vacuoles.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The obtained results for pathological damage of treated RPW larvae, R. ferrugineus, revealed that midgut was sensitive to the tested insecticides. A similar result was obtained by (Abd El-Fattah et al, 2020) who reported that the damage included vacuolation of cytoplasm, analyzes and destroyed nuclei of the epithelial cells of RPW larvae treated with imidacloprid and chlorpyrifos and their nano form as well as by (Abdel-Ghaffar, 2004) from different insecticides against different insects. Also, (Ahmed, 1995) reported that the histopathological action of some pesticides was observed to cause epithelial cell expansion and the formation of vacuoles.…”
Section: Resultssupporting
confidence: 80%
“…The basement membrane supports epithelial cells. (Abd El-Fattah et al, 2020). The obtained results for pathological damage of treated RPW larvae, R. ferrugineus, revealed that midgut was sensitive to the tested insecticides.…”
Section: Resultsmentioning
confidence: 85%
“…Synthetic insecticides are the most common control method used against R. ferrugineus and can apply in several ways. The most commonly used insecticides are chlorpyrifos, fipronil, and methomyl (El-Gohary et al, 2015), emamectin benzoate (Chihaoui-Meridja et al, 2020), imidacloprid (Abd El-Fattaha et al, 2021), and carbaryl (Hernandez-Marante et al, 2003). Insecticidal applications protect fresh injuries from adult' female infestation and prevent egg-laying (Abraham et al, 1998).…”
Section: Chemical Controlmentioning
confidence: 99%
“…P. dactylifera is subjected to damage by 112 insects and mite species in 42 families (El-Shafie, 2012). The red palm weevil, Rhynchophorus ferrugineus Olivier (Coleoptera, Curculionidae) is the most common of these pest species (Abd El-Fattaha et al, 2021). R. ferrugineus was firstly reported in the Middle East in the UAE in 1985, from where it was spreading to other countries worldwide, mainly via infested plant materials (Al-Shawaf et al, 2013;Kurdi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…RPW, commonly known as red palm weevil , Rhynchophorus ferrugineus (Olivier) (Coleoptera: Curculionidae) is documented as tremendously antagonistic palm pests with known broad economic and environmental impacts when appearing in a different geographical region ( Zhang H et al, 2020 ). RPW has a harmful social influence in the Middle-East region, where the palm tree is connected with culture and religion ( El-Fattah AYA et al, 2020 ). It is well-known as the utmost significant pest on date palm in the globe and dangerous pests for Cocos nucifera (coconut) ( Mohamed MA et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%